Titanium Carbide MXene Hole Contacts for CdTe Photovoltaics. Issue 11 (16th September 2022) - Sartor, Benjamin E.; Röhr, Jason A.; Lipton, Jason; Duenow, Joel N.; Goad, Adam; Meng, Juan; Reese, Matthew O.; Taylor, André D.
Abstract : CdTe is a high‐efficiency thin‐film photovoltaic technology that has seen tremendous commercial success over the past decade. Yet despite the improvement of other device characteristics, the fabrication of an ohmic hole back contact layer has remained a challenge due to the high ionization potential of CdTe, which limits the external potential that can be feasibly reached even as other characteristics of the device improve. MXenes, a family of 2D materials with rapidly growing scientific and commercial interest, offer a promising route to forming low‐cost, low‐barrier contacts due to their demonstrated high work function, metallic conductivity, and facile solution processing from benign solvents. Here, it is shown that Ti3 C2 T x MXene films processed from an aqueous colloidal dispersion can perform as a highly efficient hole contact material for CdTe solar cells, resulting in high power‐conversion efficiencies. The role of the Schottky barrier formation in Ti3 C2 T x ‐contacted CdTe devices is probed, and potential pathways for the future development of this potent combination of materials are elucidated. The modularity of the expansive MXene family of materials presents a promising strategy for developing next‐generation hole contacts for CdTe solar cells. Abstract : Solution‐processed Ti3 C2 T x MXene back contacts are used to make low barrier hole contacts for CdTe photovoltaic devices. Devices and contact properties are investigated to find that Ti3 C2 T x contacts have a 0.15 eV lower contact barrier than standard gold contacts and make high‐performing (>16% efficient) CdTe devices.